Foreword Anniversary of Professor Onuc Cozar - POP, Aurel (Studia Universitatis Babeș-Bolyai Physica, 2016)
Professor Onuc Cozar was born in 1946, march 29, Sancraiu-Almasului, Salaj. He graduated Babes-Bolyai University Cluj-Napoca in 1970. Since 1972 worked at “Babes-Bolyai” University, Faculty of Physics, first as teaching assistant (1970-1983), assistant professor (1983-1990) and professor (1990-present), respectively. Prof. Onuc Cozar earned in 1979 his PhD in Physics with thesis “Molecular structure and adsorption dynamics of some Cu(II) complexes determined by EPR spectroscopy”. Prof. O. Cozar was visiting professor at: University of Padova (1993), U.N.E.D. Madrid (1996), Univ. Claude Bernard Lyon (1999, 2002, 2005) and Technical University Aachen (2003), respectively.